High-performance TiO2atIn2O3 / Pd sensitive film for MEMS gas sensor, synthetic method of high-performance TiO2atIn2O3 / Pd sensitive film and MEMS gas sensor
By using TiO2@In2O3/Pd sensitive film in MEMS gas sensors, the problem of low sensitivity of a single titanium dioxide sensitive material during low gas concentration detection is solved, achieving more efficient gas detection and lower power consumption.
Patent Information
- Application Number
- CN202411334356.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-09-24
AI Technical Summary
In the prior art, a MEMS gas sensor with a single titanium dioxide as a sensitive material has low sensitivity when detecting the gas lower limit, making it difficult to effectively detect gases when the gas concentration is low.
TiO2@In2O3/Pd sensitive film was used to synthesize mesoporous TiO2 nanoparticle spheres, and coat In2O3 and modify Pd by hydrothermal reaction to form a high-performance sensitive film.
It improves the sensitivity of gas detection, enhances the response ability to low gas concentration, reduces device power consumption and improves safety performance.
Smart Images

Figure CN119407187A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sensitive materials, and more specifically, relates to a high performance TiO2 for MEMS gas sensors. 2 @In 2 O 3 / Pd sensitive film, its synthesis method and MEMS gas sensor. Background Art
[0002] Semiconductor gas sensors detect the composition or concentration of gas by using the change in resistance of semiconductor sensitive materials when they come into contact with gas. The gas undergoes an oxidation-reduction reaction with the sensitive material, causing the resistance of the sensitive material to change. Gas detection is achieved by detecting the change in resistance.
[0003] Titanium dioxide (TiO 2 ) is an excellent photocatalytic material, which shows excellent catalytic activity under light excitation. The excited titanium dioxide can undergo oxidation reaction with volatile organic compounds to change its resistance value. Therefore, it can be used to detect volatile organic compounds (VOCs) gas, especially in H 2 Titanium dioxide has certain potential value in the detection of S. Therefore, titanium dioxide is currently commonly used as a semiconductor sensitive material for gas sensors to make titanium dioxide sensors.
[0004] However, when using single titanium dioxide as the sensitive material, the lower limit of gas detection is high, and it is difficult to trigger a response when the gas concentration is low, or the response is weak, that is, the sensitivity of gas detection is low. Summary of the invention
[0005] In view of the above defects or improvement needs of the prior art, the present invention provides a high-performance TiO 2 @In 2 O 3 / Pd sensitive film, its synthesis method and MEMS gas sensor, the purpose of which is to improve the sensitivity of gas detection.
[0006] To achieve the above object, the present invention provides a high performance TiO 2 @In 2 O 3 / Pd sensitive thin film synthesis method, which comprises:
[0007] Step S1: Synthesis of mesoporous TiO 2 Nanoparticle spheres;
[0008] Step S2: firstly mix indium salt, alkaline compound, surfactant and the mesoporous TiO2 The nanoparticles are mixed evenly and then subjected to a hydrothermal reaction. The product of the hydrothermal reaction is centrifuged, washed, and dried, and then subjected to a first annealing treatment in an air atmosphere to obtain In 2 O 3 Coated titanium dioxide nanoparticles TiO 2 @In 2 O 3 ;
[0009] Step S3: Adding TiO nanoparticles to the nanoparticles by solution method 2 @In 2 O 3 The modified palladium nanoparticles were centrifuged, washed and dried, and then annealed for the second time in a hydrogen atmosphere to obtain In 2 O 3 Pd-coated titanium dioxide nanoparticles TiO 2 @In 2 O 3 / Pd;
[0010] Step S4: The nanoparticles TiO 2 @In 2 O 3 / Pd is used to make the sensitive film.
[0011] In an optional embodiment, in step S1, the synthesized mesoporous TiO 2 Nanoparticle spheres, including:
[0012] Step S11: dissolving a structure-directing agent alkylamine in ethanol and stirring to form a transparent solution;
[0013] Step S12: stirring the transparent solution and adding a strong base and a strong acid salt during the stirring period, then adding polyol titanium and mixing them evenly, and letting the solution stand to form a stable precipitate;
[0014] Step S13: centrifuging, washing and drying the precipitate after standing to obtain a powder;
[0015] Step S14: uniformly mixing the powder, ethanol and water and performing a hydrothermal reaction;
[0016] Step S15: Centrifuge, wash and dry the product of the hydrothermal reaction to obtain the mesoporous TiO 2 Nanoparticle spheres.
[0017] In an optional embodiment, the structure-directing agent alkylamine comprises one or more of methaneamine, dodecylamine or hexadecylamine, and the strong base and strong acid salt comprises KCl, NaCl or NaNO 3One or more of the polyol titanium includes one or more of titanium isopropoxide, titanium ethylene glycol and titanium tetra-n-butoxide;
[0018] In step S11 and step S12, the ratio of structure-directing agent alkylamine, ethanol, strong base strong acid salt, and titanium isopropoxide is as follows: (0.1-2.0) g structure-directing agent alkylamine: (18-22) ml ethanol: (0.3-0.5) ml 0.1 M strong base strong acid salt: (4-6) ml titanium isopropoxide;
[0019] In step S14, the ratio of powder, ethanol and water satisfies: (0.8-1.2) g powder: (18-22) ml ethanol: (8-12) ml water.
[0020] In an optional embodiment, in step S2, the indium salt comprises one or more of indium nitrate, indium chloride or indium acetate, the alkaline compound comprises sodium citrate, and the surfactant comprises urea.
[0021] In an optional embodiment, in step S3, the nanoparticle spheres TiO 2 @In 2 O 3 Modified palladium nanoparticles, including:
[0022] The nanoparticle spheres TiO 2 @In 2 O 3 , palladium salt, palladium salt reducing agent and deionized water are evenly mixed, and the palladium salt reducing agent is used to reduce the high-valent palladium ions in the palladium salt into palladium element and embed it into the nanoparticle ball TiO 2 @In 2 O 3 middle.
[0023] In an optional embodiment, the nanoparticle sphere TiO 2 @In 2 O 3 The ratio of palladium to titanium atoms is in the range of 0.1% to 5%.
[0024] In an optional embodiment, the annealing temperature of the first annealing treatment is 450°C to 550°C; the annealing temperature of the second annealing treatment is 250°C to 350°C.
[0025] In an optional embodiment, in step S4, the nanoparticle spheres TiO 2 @In 2 O 3 / Pd is made into the sensitive film, comprising:
[0026] The TiO nanoparticle spheres were self-assembled at the air / water interface.2 @In 2 O 3 / Pd is used to make the sensitive film.
[0027] The present invention also provides a high performance TiO2 for MEMS gas sensor. 2 @In 2 O 3 / Pd sensitive film, the sensitive film is composed of nanoparticle spheres TiO 2 @In 2 O 3 / Pd, the nanoparticle spheres are TiO 2 @In 2 O 3 / Pd is In 2 O 3 Titanium dioxide nanoparticle spheres coated and modified with Pd.
[0028] The present invention also provides a MEMS gas sensor, comprising the high performance TiO 2 @In 2 O 3 / Pd sensitive film.
[0029] In general, compared with the prior art, the above technical solutions conceived by the present invention mainly have the following beneficial effects:
[0030] High performance TiO2 for MEMS gas sensor provided by the present invention 2 @In 2 O 3 / Pd sensitive thin film synthesis method, first synthesize mesoporous TiO 2 Nanoparticle spheres were then synthesized by hydrothermal reaction. 2 O 3 And coated with mesoporous TiO 2 Nanoparticle spheres, to obtain nanoparticle spheres TiO 2 @In 2 O 3 Then, palladium nanoparticles were used to modify the TiO nanoparticles. 2 @In 2 O 3 / Pd, and finally the obtained nanoparticle spheres TiO 2 @In 2 O 3 / Pd is made into a sensitive film. In the present invention, TiO 2 Nanoparticle spheres, TiO 2 It is an excellent photoexcitation material and exhibits excellent photocatalytic activity under UV light. 2Nanoparticle balls are the main structure of the sensitive film, and light activation can be used to activate the sensitive film. Compared with thermal activation, it can reduce device power consumption and has higher safety performance. In the present invention, the nanoparticle balls have a mesoporous structure, which can increase the specific surface area of the nanoparticle balls and is more conducive to the adsorption of substances. 2 After the nanoparticles are spherical, In 2 O 3 Coated TiO 2 Nanoparticle spheres, due to TiO 2 Although it has excellent light activation properties, its gas sensing performance is poor. 2 O 3 Coating it can increase the carrier concentration and mobility, making it easier for the sensitive film to migrate electrons, thereby improving the conductivity of the sensitive film and then improving the sensitivity of the sensitive film to gas detection. 2 O 3 The coating will hinder the light to the matrix TiO 2 In order to compensate for the irradiation rate, the present invention further utilizes palladium nanoparticles for modification. Pd nanoparticles can modify nanoparticles to achieve chemical sensitization and electronic sensitization. Chemical sensitization utilizes the catalytic properties of Pd nanoparticles to increase the oxidation reaction rate of gas and sensitive film, thereby improving the effectiveness of gas detection. Electronic sensitization utilizes the fact that Pd nanoparticles can also undergo different degrees of oxidation reaction according to different gas atmospheres, thereby affecting the resistance of the sensitive film and further improving the sensitivity to gas detection. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 A high performance TiO2 for a MEMS gas sensor in one embodiment of the present invention 2 @In 2 O 3 / Flow chart of the steps of the Pd sensitive film synthesis method;
[0032] Figure 2 The mesoporous TiO 2 SEM images of nanoparticle spheres;
[0033] Figure 3 The nanoparticle sphere TiO 2 @In 2 O 3 / Pd component mapping diagram;
[0034] Figure 4 The SEM images of different nanoparticles, among which (a) is TiO 2 SEM images at different scales, (b) TiO2 @10In 2 O 3 SEM images at different scales, (c) is TiO 2 @20In 2 O 3 SEM images at different scales, (d) is TiO 2 @30In 2 O 3 SEM images at different scales;
[0035] Figure 5 The gas sensors made of different nanoparticles react with H under UV light excitation. 2 Response curve diagram of S gas, where (a) is the resistance change curve and (b) is the response change curve;
[0036] Figure 6 This is the relationship between the dynamic response of the gas sensor made of different nanoparticle balls and the gas concentration;
[0037] Figure 7 1 is a SEM image of a MEMS sensor and its sensitive film in one embodiment of the present invention, wherein (a) is a MEMS sensor wafer structure, (b) is a group of interdigitated structures in the MEMS sensor, (c) is a top view of the sensitive film, and (d) is a front view of the sensitive film. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0039] The present invention provides a high performance TiO2 for MEMS gas sensor. 2 @In 2 O 3 / Pd sensitive thin film synthesis method, such as Figure 1 The figure shows a high performance TiO2 for MEMS gas sensor in one embodiment of the present invention. 2 @In 2 O 3 / Pd sensitive thin film synthesis method, the method comprises steps S1 to S4, and the steps are introduced below.
[0040] Step S1: Synthesis of mesoporous TiO 2 Nanoparticle spheres.
[0041] Specifically, mesoporous TiO can be synthesized using conventional methods. 2 Nanoparticle spheres, such as mesoporous TiO, can be synthesized under the action of structure-directing agents such as alkylamines and strong bases and salts. 2 .
[0042] In one embodiment, mesoporous TiO can be synthesized by the following five steps: 2 Nanoparticle spheres.
[0043] Step S11: dissolving a structure-directing agent alkylamine in ethanol and stirring to form a transparent solution.
[0044] Step S12: Stir the transparent solution and add a strong base or a strong acid salt during the stirring period, then add polyol titanium and mix well, and let the solution stand to allow a stable precipitate to form.
[0045] In the specific operation, add the strong base and strong acid salt while stirring the transparent solution, so that the reaction can be more complete. After the strong base and strong acid salt are added, add polyol titanium, stir vigorously at room temperature to mix the reagents evenly, and then let it stand for a period of time so that the solution becomes a stable precipitate. Generally, it needs to stand for 15h to 20h, for example, 18h.
[0046] In this process, polyol titanium provides the titanium source, and strong base and strong salt act as templates to regulate the mesoporous structure.
[0047] The structure-directing agent alkylamine includes one or more of methaneamine, dodecylamine or hexadecylamine, and the strong base and strong acid salt include KCl, NaCl or NaNO 3 One or more of the polyol titanium includes titanium isopropoxide, titanium glycol and titanium tetra-n-butoxide.
[0048] In the above steps, the ratio of structure-directing agent alkylamine, ethanol, strong base and strong acid salt, and polyol titanium can be adjusted to achieve the effect of mesoporous TiO 2 Control of pore structure and size. In a preferred embodiment, the ratio of structure-directing agent alkylamine, ethanol, strong base strong acid salt, and titanium isopropoxide satisfies: (0.1-2.0) ml structure-directing agent alkylamine: (18-22) ml ethanol: (0.3-0.5) ml 0.1 M strong base strong acid salt: (4-6) ml titanium isopropoxide. Under this ratio, the obtained precursor can be used to synthesize TiO2 with uniform size and mesoporous structure.
[0049] Step S13: centrifuging, washing and drying the precipitate after standing to obtain a powder.
[0050] At this point, the obtained powder is the precursor of mesoporous TiO2.
[0051] Step S14: uniformly mix the powder, ethanol and water and perform a hydrothermal reaction.
[0052] At this time, mesoporous TiO can be generated through hydrothermal reaction. 2 Nanoparticle balls. In specific operations, the temperature range of the hydrothermal reaction can be 130°C to 170°C, for example, can be set to 150°C.
[0053] During the specific operation, the ratio of powder, ethanol and water meets the following requirements: (0.8-1.2) g powder: (18-22) ml ethanol: (8-12) ml water.
[0054] Step S15: Centrifuge, wash and dry the product of the hydrothermal reaction to obtain mesoporous TiO 2 Nanoparticles. It is understandable that, since no annealing treatment has been performed, organic matter may still remain in the sample obtained at this time, and the residue is removed in the annealing operation in step S2. The fact that no annealing is performed in step S1 is also to facilitate the realization of In step S2. 2 O 3 The covering.
[0055] like Figure 2 As shown, the obtained TiO 2 Nanoparticles have mesoporous structures, TiO 2 The pore size of the nanoparticles can be controlled within the range of 2 to 50 nm. Within this size range, the nanoparticles exhibit mesoporous structural characteristics. In a preferred embodiment, the ratio of the reagents is adjusted so that the TiO 2 The size distribution of the nanoparticle spheres is more uniform, which is beneficial to improving the consistency of the sensor's dynamic response to gas.
[0056] In the synthesis of mesoporous TiO 2 After the nanoparticles are formed, step S2 is performed.
[0057] Step S2: First, indium salt, alkaline compound, surfactant and mesoporous TiO 2 The nanoparticles are mixed evenly and then subjected to a hydrothermal reaction. The product of the hydrothermal reaction is centrifuged, washed, and dried, and then subjected to a first annealing treatment in an air atmosphere to obtain In 2 O 3 Coated titanium dioxide nanoparticles TiO 2 @In 2 O 3 .
[0058] At this time, through the hydrothermal reaction, In 2 O 3 In TiO 2 Surface nucleation and growth to generate In 2 O 3 Coated TiO 2The role of the surfactant is to promote the In 2 O 3 Rapid nucleation. In specific operation, the temperature range of the hydrothermal reaction can be 110°C to 150°C, for example, it can be set to 130°C.
[0059] The indium salt comprises one or more of indium nitrate, indium chloride or indium acetate, the alkaline compound comprises sodium citrate, and the surfactant comprises urea.
[0060] In this step, the indium salt and mesoporous TiO 2 The ratio of nanoparticles is used to achieve In 2 O 3 Control of the coating amount, in a preferred embodiment, indium salt, mesoporous TiO 2 The ratio of the nanoparticle balls meets the following requirements: (0.01-1.0) g: 0.1 g. Within this range, the performance of the sensor is significantly improved.
[0061] After the hydrothermal reaction, the hydrothermal product is centrifuged, washed and dried, and subjected to a first annealing heat treatment in an air atmosphere. By annealing in an air atmosphere, the mesoporous TiO 2 , thus obtaining In 2 O 3 Coated titanium dioxide nanoparticles TiO 2 @In 2 O 3 In a specific embodiment, the annealing temperature of the first annealing heat treatment can be selected from 450°C to 550°C, and the annealing time can be selected from 1.5h to 2.5h. For example, annealing at 500°C for 2h can be selected to obtain nanoparticle spheres of TiO 2 @In 2 O 3 .
[0062] Step S3: Prepare TiO nanoparticles by solution method 2 @In 2 O 3 The modified palladium nanoparticles were centrifuged, washed and dried, and then annealed for the second time in a hydrogen atmosphere to obtain In 2 O 3 Pd-coated titanium dioxide nanoparticles TiO 2 @In 2 O 3 / Pd.
[0063] Specifically, the nanoparticles TiO 2 @In 2 O 3, palladium salt, palladium salt reducing agent and deionized water are mixed evenly. The palladium salt reducing agent can reduce the high-valent palladium ions in the palladium salt into palladium element and embed it into the nanoparticle ball TiO 2 @In 2 O 3 In actual operation, the content of palladium atoms can be flexibly adjusted to adjust the response characteristics of the sensor. For example, in the nanoparticle sphere TiO 2 @In 2 O 3 In the embodiment, the ratio of the number of palladium atoms to that of tin atoms is in the range of 0.1% to 5%, within which a good Pd particle modification effect can be achieved. In one embodiment, the palladium salt can be selected from one or more of dichlorotetraamminepalladium, palladium nitrate and palladium chloride, and the palladium salt reducing agent is generally selected from sodium borohydride.
[0064] After the reaction, the product is centrifuged, washed, dried, and annealed for the second time in a hydrogen atmosphere. By annealing in a hydrogen atmosphere, the well-oxidized Pd can be reduced to zero-valent Pd, thereby obtaining In 2 O 3 Pd-coated titanium dioxide nanoparticles TiO 2 @In 2 O 3 In a specific embodiment, the annealing temperature of the second annealing heat treatment can be selected from 250°C to 350°C, and the annealing time can be selected from 1.5h to 2.5h. For example, annealing at 300°C for 2h can be selected to obtain nanoparticle spheres TiO 2 @In 2 O 3 / Pd.
[0065] like Figure 3 The nanoparticle sphere TiO in one embodiment is shown. 2 @In 2 O 3 / Pd composition mapping diagram, it can be seen from the figure that the nanoparticle sphere TiO 2 @In 2 O 3 / Pd contains Ti, O, In, and Pd, indicating that in TiO 2 In and Pd were successfully added to the nanoparticle spheres.
[0066] Step S4: TiO nanoparticles 2 @In 2 O 3 / Pd is made into a sensitive film.
[0067] In a preferred embodiment, the nanoparticle spheres TiO 2 @In2 O 3 / Pd is made into a sensitive film, and the specific operation is as follows:
[0068] The nanoparticles were first treated with dodecyl for hydrophobicity and then prepared into TiO 2 @In 2 O 3 / Pd nanoparticle sphere ethanol dispersion, and finally drop the dispersion drop by drop on the inner wall of a beaker containing deionized water, eventually forming a single-layer nanoparticle sphere film at the water / air interface, and finally the corresponding device film and wafer film can be obtained by the method of scooping the film from a MEMS device or wafer.
[0069] In specific operations, the composition ratio of indium salt can be adjusted to control In 2 O 3 The coating amount can be adjusted to adjust the sensitivity of the gas sensor.
[0070] The following selections are In(NO 3 ) 3 Taking indium salt as an example, a comparison of sensor performance under several different ratios of indium and titanium atoms is given.
[0071] Comparative Example
[0072] (1) Dissolve 0.5 g of hexadecylamine in 20 ml of ethanol and stir to form a transparent solution. Then add 0.4 ml of 0.1 M KCl to the solution while stirring. Add 5 ml of titanium isopropoxide to the solution, stir vigorously at room temperature, and let stand for 18 h. Then centrifuge, wash, and dry to obtain a powder. Mix 1.0 g of the dry powder with 20 ml of ethanol and 10 ml of H 2 O to form a mixed solution, and finally subjected to hydrothermal reaction at 150 °C for 24 h;
[0073] (2) The hydrothermal product obtained in step (1) is centrifuged, washed and dried, and annealed at 500° C. for 2 h in an air atmosphere. The obtained sample is labeled as nanoparticle sphere TiO 2 .
[0074] Example 1
[0075] (1) Dissolve 0.5 g of hexadecylamine in 20 ml of ethanol and stir to form a transparent solution. Then add 0.4 ml of 0.1 M KCl to the solution while stirring. Add 5 ml of titanium isopropoxide to the solution, stir vigorously at room temperature, and let stand for 18 h. Then centrifuge, wash, and dry to obtain a powder. Mix 1.0 g of the dry powder with 20 ml of ethanol and 10 ml of H 2 O to form a mixed solution, and finally subjected to hydrothermal reaction at 150 °C for 24 h;
[0076] (2) 0.1 g of the sample obtained in (1) was mixed with 0.1 g of indium nitrate (In(NO 3 ) 3 4.5H 2 O), 0.1g sodium citrate (C 6 H 5 Na 3 O 7 ), 0.025 g urea and 40 ml deionized water were mixed, and then transferred to a reactor, and then hydrothermally reacted at a temperature of 130 ° C for 6 h;
[0077] (3) The hydrothermal product obtained in step (2) is centrifuged, washed and dried, and annealed at 500° C. for 2 h in an air atmosphere. The obtained sample is labeled as nanoparticle sphere TiO 2 @10In 2 O 3 .
[0078] Example 2
[0079] (1) Dissolve 0.5 g of hexadecylamine in 20 ml of ethanol and stir to form a transparent solution. Then add 0.4 ml of 0.1 M KCl to the solution while stirring. Add 5 ml of titanium isopropoxide to the solution, stir vigorously at room temperature, and let stand for 18 h. Then centrifuge, wash, and dry to obtain a powder. Mix 1.0 g of the dry powder with 20 ml of ethanol and 10 ml of H 2 O to form a mixed solution, and finally subjected to hydrothermal reaction at 150 °C for 24 h;
[0080] (2) 0.1 g of the sample obtained in (1) was mixed with 0.2 g of indium nitrate (In(NO 3 ) 3 4.5H 2 O), 0.2g sodium citrate (C 6 H 5 Na 3 O 7 ), 0.030 g urea and 40 ml deionized water, then transferred to a reactor, and then subjected to a hydrothermal reaction at 130 °C for 6 h;
[0081] (3) The hydrothermal product obtained in step (2) is centrifuged, washed and dried, and annealed at 500° C. for 2 h in an air atmosphere. The obtained sample is labeled as nanoparticle sphere TiO 2 @20In 2 O 3 .
[0082] Example 3
[0083] (1) Dissolve 0.5 g of hexadecylamine in 20 ml of ethanol and stir to form a transparent solution. Then add 0.4 ml of 0.1 M KCl to the solution while stirring. Add 5 ml of titanium isopropoxide to the solution, stir vigorously at room temperature, and let stand for 18 h. Then centrifuge, wash, and dry to obtain a powder. Mix 1.0 g of the dry powder with 20 ml of ethanol and 10 ml of H 2 O to form a mixed solution, and finally subjected to hydrothermal reaction at 150 °C for 24 h;
[0084] (2) 0.1 g of the sample obtained in (1) was mixed with 0.3 g of indium nitrate (In(NO 3 ) 3 4.5H 2 O), 0.3g sodium citrate (C 6 H 5 Na 3 O 7 ), 0.045 g urea and 40 ml deionized water, and then transferred to a reactor, and then subjected to a hydrothermal reaction at a temperature of 130 ° C for 6 h;
[0085] (3) The hydrothermal product obtained in step (2) is centrifuged, washed and dried, and annealed at 500° C. for 2 h in an air atmosphere. The obtained sample is labeled as nanoparticle sphere TiO 2 @30In 2 O 3 .
[0086] Example 4
[0087] (1) Dissolve 0.5 g of hexadecylamine in 20 ml of ethanol and stir to form a transparent solution. Then add 0.4 ml of 0.1 M KCl to the solution while stirring. Add 5 ml of titanium isopropoxide to the solution, stir vigorously at room temperature, and let stand for 18 h. Then centrifuge, wash, and dry to obtain a powder. Mix 1.0 g of the dry powder with 20 ml of ethanol and 10 ml of H 2 O to form a mixed solution, and finally subjected to hydrothermal reaction at 150 °C for 24 h;
[0088] (2) 0.1 g of the sample obtained in (1) was mixed with 0.2 g of indium nitrate (In(NO 3 ) 3 4.5H 2 O), 0.2g sodium citrate (C 6 H 5 Na 3 O 7 ), 0.030 g urea and 40 ml deionized water, then transferred to a reactor, and then subjected to a hydrothermal reaction at 130 °C for 6 h;
[0089] (3) The hydrothermal product obtained in step (2) is centrifuged, washed and dried, and annealed at 500° C. for 2 h in an air atmosphere.
[0090] (4) 0.1 g of the sample obtained in step (3) was mixed evenly with 0.005 g of dichlorotetraamminepalladium, 0.1 g of sodium borohydride, and 10 ml of deionized water, and then centrifuged, washed, and dried.
[0091] (5) The sample obtained in step (4) was annealed at 300°C in a hydrogen atmosphere, and the obtained sample was labeled as nanoparticle sphere TiO 2 @20In 2 O 3 / Pd.
[0092] like Figure 4 The SEM images of different nanoparticle spheres are shown, among which (a) is TiO 2 SEM images at different scales, (b) TiO 2 @10In 2 O 3 SEM images at different scales, (c) is TiO 2 @20In 2 O 3 SEM images at different scales, (d) is TiO 2 @30In 2 O 3 SEM images at different scales.
[0093] like Figure 5 The results show that the gas sensors made of different nanoparticles react with H under UV light excitation. 2 The response curve of S gas, where (a) is the resistance change curve and (b) is the response change curve. It can be seen from the figure that compared with pure TiO 2 Nanoparticle spheres, whether only In 2 O 3 Wrapping is still in progress 2 O 3 The response characteristics of the corresponding gas sensors were improved by palladium modification on the basis of In coating. 2 O 3 Wrapping, In 2 O 3 The effect of the material obtained by palladium modification on the basis of coating is better.
[0094] like Figure 6 The figure shows the relationship between the dynamic response of the gas sensor made of different nanoparticles and the gas concentration. 2 Nanoparticles, only In2 O 3 Coated TiO 2 @In 2 O 3 Nanoparticle spheres and In 2 O 3 Pd-coated TiO 2 @In 2 O 3 / Pd corresponding to the sensor, TiO 2 @In 2 O 3 Better than TiO 2 , TiO 2 @In 2 O 3 / Pd is superior to TiO 2 @In 2 O 3 , which shows that the technical solution of the present invention can improve the sensitivity of the sensor to gas detection.
[0095] Accordingly, the present invention also relates to a high performance TiO 2 @In 2 O 3 / Pd sensitive film, the sensitive film is composed of nanoparticle spheres TiO 2 @In 2 O 3 / Pd, nanoparticle spheres TiO 2 @In 2 O 3 / Pd is In 2 O 3 The titanium dioxide nanoparticle spheres coated and modified with Pd. Specifically, the sensitive film can be synthesized by the synthesis method described above.
[0096] Accordingly, the present invention also relates to a MEMS gas sensor, which comprises the sensitive film described above. Specifically, the gas sensor comprises a MEMS chip and a sensitive film covering the surface of the MEMS chip, such as Figure 7 The figure shows a structural diagram of a MEMS sensor formed in an embodiment and a SEM image of its sensitive film. The target gas in the environment will undergo an oxidation reaction with the sensitive film to cause the resistance of the sensitive film to change. The MEMS chip detects the target gas by detecting the resistance of the sensitive film.
[0097] The technical features of the above-mentioned embodiments can be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above-mentioned embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. It should be noted that "in one embodiment", "for example", "for example", etc. of the present invention are intended to illustrate the present invention, rather than to limit the present invention.
[0098] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent application. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A method for synthesizing a high-performance TiO2@In2O3 / Pd sensitive thin film for MEMS gas sensors, characterized in that: include: Step S1: synthesizing mesoporous TiO2 nanoparticle spheres; Step S2: firstly, the indium salt, the alkaline compound, the surfactant and the mesoporous TiO2 nanoparticle ball are uniformly mixed and then subjected to a hydrothermal reaction, and then the product of the hydrothermal reaction is centrifuged, washed and dried, and then subjected to a first annealing treatment in an air atmosphere to obtain In2O3-coated titanium dioxide nanoparticle ball TiO2@In2O3; Step S3: modifying the nanoparticle sphere TiO2@In2O3 with palladium nanoparticles by a solution method, centrifuging, washing and drying, and then performing a second annealing treatment in a hydrogen atmosphere to obtain In2O3-coated and Pd-modified titanium dioxide nanoparticle spheres TiO2@In2O3 / Pd; Step S4: preparing the nanoparticle spheres TiO2@In2O3 / Pd into the sensitive film.
2. The method for synthesizing a high-performance TiO2@In2O3 / Pd sensitive thin film for a MEMS gas sensor according to claim 1, characterized in that: In step S1, the synthesis of mesoporous TiO2 nanoparticle spheres comprises: Step S11: dissolving a structure-directing agent alkylamine in ethanol and stirring to form a transparent solution; Step S12: stirring the transparent solution and adding a strong base and a strong acid salt during the stirring period, then adding polyol titanium and mixing them evenly, and letting the solution stand to form a stable precipitate; Step S13: centrifuging, washing and drying the precipitate after standing to obtain a powder; Step S14: uniformly mixing the powder, ethanol and water and performing a hydrothermal reaction; Step S15: centrifuging, washing and drying the product of the hydrothermal reaction to obtain the mesoporous TiO2 nanoparticle spheres.
3. The method for synthesizing a high-performance TiO2@In2O3 / Pd sensitive thin film for a MEMS gas sensor according to claim 2, characterized in that: The structure-directing agent alkylamine includes one or more of methaneamine, dodecylamine or hexadecylamine, the strong base and strong acid salt include one or more of KCl, NaCl or NaNO3, and the polyol titanium includes one or more of titanium isopropoxide, titanium ethylene glycol and titanium tetra-n-butoxide; In step S11 and step S12, the ratio of structure-directing agent alkylamine, ethanol, strong base strong acid salt, and titanium isopropoxide is as follows: (0.1-2.0) g structure-directing agent alkylamine: (18-22) ml ethanol: (0.3-0.5) ml 0.1 M strong base strong acid salt: (4-6) ml titanium isopropoxide; In step S14, the ratio of powder, ethanol and water satisfies: (0.8-1.2) g powder: (18-22) ml ethanol: (8-12) ml water.
4. The method for synthesizing a high-performance TiO2@In2O3 / Pd sensitive thin film for a MEMS gas sensor according to claim 1, characterized in that: In step S2, the indium salt comprises one or more of indium nitrate, indium chloride or indium acetate, the alkaline compound comprises sodium citrate, and the surfactant comprises urea.
5. The method for synthesizing a high-performance TiO2@In2O3 / Pd sensitive thin film for a MEMS gas sensor according to claim 1, characterized in that: In step S3, palladium nanoparticles are modified on the nanoparticle spheres TiO2@In2O3 by a solution method, comprising: The nanoparticle ball TiO2@In2O3, palladium salt, palladium salt reducing agent and deionized water are mixed evenly. The palladium salt reducing agent is used to reduce the high-valent palladium ions in the palladium salt into a single palladium substance and embed it into the nanoparticle ball TiO2@In2O3.
6. The method for synthesizing a high-performance TiO2@In2O3 / Pd sensitive thin film for a MEMS gas sensor according to claim 1, characterized in that: In the nano-particle sphere TiO2@In2O3, the ratio of the number of palladium atoms to that of titanium atoms ranges from 0.1% to 5%.
7. The method for synthesizing a high-performance TiO2@In2O3 / Pd sensitive thin film for a MEMS gas sensor according to claim 1, characterized in that: The annealing temperature of the first annealing treatment is 450°C to 550°C; the annealing temperature of the second annealing treatment is 250°C to 350°C.
8. The method for synthesizing a high-performance TiO2@In2O3 / Pd sensitive thin film for a MEMS gas sensor according to claim 1, characterized in that: In step S4, the step of making the nanoparticle spheres TiO2@In2O3 / Pd into the sensitive film comprises: The nanoparticle sphere TiO2@In2O3 / Pd is made into the sensitive film through an air / water interface self-assembly method.
9. A high-performance TiO2@In2O3 / Pd sensitive film for MEMS gas sensor, characterized in that: The sensitive film is made of nanoparticle balls TiO2@In2O3 / Pd, and the nanoparticle balls TiO2@In2O3 / Pd are titanium dioxide nanoparticle balls coated with In2O3 and modified with Pd.
10. A MEMS gas sensor, characterized in that: It comprises the high-performance TiO2@In2O3 / Pd sensitive film as described in claim 9.
Citation Information
Patent Citations
Preparation method of gas sensor with indium oxide nanoparticle / titanium dioxide nanobelt heterostructure
CN106814112A
Acetone sensor with Pt-ZnO-In2O3 composite nanofiber as sensitive material, and preparation method and application thereof
CN108802114A
Pd / In2O3 gas sensitive material, preparation method thereof and gas sensitive sensor
CN113670989A
Method for preparing multi-color photochromic Ag / TiO2 film
CN114427112A
Preparation of hydrogen MEMS gas sensor based on Pd modified titanium dioxide nano material, and product and application thereof
CN115343333A